The Effect of Mudharabah Financing on MSME Customer Income - Ayushandra Saskiaputri; Trisni Handayani (Universitas Islam Negeri Alauddin Makassar, 2024)
Indonesia's rapid economic growth demands the vital role of MSMEs in supporting economic development. However, in reality, MSMEs often face obstacles in developing their businesses. As an Islamic financial institution, BMT is expected to provide solutions with mudharabah financing in helping MSMEs develop their business and increase their business income. This study aims to determine the effect of mudharabah financing on the income of MSME customers at BMT Riyadhul Jannah. The research method used by researchers in this study is a quantitative method with a type of survey method. The population in this study was 200 customers, with a sample size of 30 MSME customers who used mudharabah financing. The data collection technique is using observation and distributing questionnaires or questionnaires. Based on the results of the study, it shows that mudharabah financing has a positive impact on the income of MSME customers at BMT Riyadhul Jannah.